Combustion of Polycarbonate and Polycarbonate–Carbon Nanotube Composites Using Fluidized Bed Technology - Lakhdar Sidi Salah; Gabriela Berkowicz-Płatek; Witold Żukowski; Yann Danlée; Isabelle Huynen; Kinga Wencel; Jan Wrona; Dawid Taler (Energies)
This study investigates the combustion behavior of polycarbonate (PC) and polycarbonate–carbon nanotube (PC-CNT) composites in fluidized bed reactors. The primary objective was to evaluate the influence of carbon nanotubes (CNTs) on the thermal stability and combustion efficiency of PC. Simultaneous thermogravimetric and differential scanning calorimetry (TG-DSC) analyses were conducted under both air and oxygen-deficient conditions to assess decomposition temperature ranges and energetic effects. Additionally, a simultaneous TG-DSC analysis of the samples’ decomposition in a 2 vol.% O2 atmosphere was carried out to simulate adverse combustion conditions that may occur in some combustion technologies, such as the accumulation of degraded material on the grate. Combustion experiments were performed in inert and catalytic fluidized beds, the latter incorporating Fe2O3-coated cenospheres to enhance catalytic activity. The results demonstrated that the presence of CNTs alters the combustion mechanism, reducing energy release in the initial degradation stage while significantly intensifying exothermic effects in subsequent stages. Under oxygen-deficient conditions, both PC and PC-CNT required higher temperatures and extended times for complete decomposition. The catalytic fluidized bed markedly improved combustion efficiency at lower temperatures, achieving up to 90% conversion at 550 °C, compared to inert beds that required 750 °C for similar efficiency.